HOW ENJOYMENT, TRUST IN INTENTION WHEN CHOOSING A SHOPPING PLACE - Rusiyati, Sri; Suleman, Dede; Riftiasari, Dinar; Suharyadi, Dedi; Marwansyah, Sofyan; Sabil, Sabil (Dinasti International Journal of Management Science, 2021)
The importance of analyzing the relationship between enjoyment and trust in consumer buying interest before making shopping decisions. This study used a sampling quota sampling technique with a survey method with a total sample size of 100 respondents from the city of Jakarta with the criteria for respondents who were over 20 years old. The results of the study indicate that enjoyment and trust influence consumer purchase orders. Therefore, a good marketer must build these two factors in the place of shopping because they can trigger requests to buy and later become a stimulus in purchasing decisions.